Fine-Grained Nociceptive Maps in Primary Somatosensory Cortex - Mancini, Flavia (Society for Neuroscience, 2012)
Topographic maps of the receptive surface are a fundamental feature of neural organization in many sensory systems. While touch is finely mapped in the cerebral cortex, it remains controversial how precise any cortical nociceptive map may be. Given that nociceptive innervation density is relatively low on distal skin regions such as the digits, one might conclude that the nociceptive system lacks fine representation of these regions. Indeed, only gross spatial organization of nociceptive maps has been reported so far. However, here we reveal the existence of fine-grained somatotopy for nociceptive inputs to the digits in human primary somatosensory cortex (SI). Using painful nociceptive-selective laser stimuli to the hand, and phase-encoded functional magnetic resonance imaging analysis methods, we observed somatotopic maps of the digits in contralateral SI. These nociceptive maps were highly aligned with maps of non-painful tactile stimuli, suggesting comparable cortical representations for, and possible interactions between, mechanoreceptive and nociceptive signals. Our findings may also be valuable for future studies tracking the time course and the spatial pattern of plastic changes in cortical organization involved in chronic pain.